Thrombin Activatable Fibrinolysis Inhibitor (TAFI) Levels in Patients with Coronary Artery Disease Investigated by Angiography - Schroeder, Verena; Chatterjeel, Tushar; Mehta, Haresh; Windecker, Stephan; Pham, Trinh; Devantay, Nicolas; Meier, Bernhard; Kohler, Hans P. (Thrombosis and Haemostasis, 2002)
Due to its role in the balance between coagulation and fibrinolysis, thrombin activatable fibrinolysis inhibitor (TAFI) may be involved in the development of cardiovascular diseases. We studied 362 patients with coronary artery disease (CAD) and 134 control subjects free of CAD, both groups investigated by angiography. TAFI antigen levels were determined in venous and intracoronary plasma samples and were related to metabolic and hemostatic risk factors and extent of coronary atherosclerosis. Venous TAFI levels tended to be higher in CAD patients compared to controls, whereas this difference was significant in intracoronary samples. A subgroup of patients who had not experienced acute myocardial infarction or undergone previous cardiac interventions showed significantly higher TAFI levels in both venous and intracoronary plasma samples. TAFI levels correlated with acute phase reactants indicating a role for TAFI in inflammation. However, TAFI levels did not correlate with extent of coronary atherosclerosis and among the classical cardiovascular risk factors TAFI levels only correlated with total cholesterol and fibrinogen concentration. Our results suggest that TAFI might be a risk factor for the development of CAD.
Keywords: Thrombin activatable fibrinolysis inhibitor; TAFI; procarboxypeptidase; coronary artery disease